1993
DOI: 10.1007/bf01709278
|View full text |Cite
|
Sign up to set email alerts
|

Management of atrial tachyarrhythmias in the critically ill: A comparison of intravenous procainamide and amiodarone

Abstract: Procainamide and amiodarone appear to be safe and equally effective in the treatment of AT in the critically ill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 13 publications
1
31
1
Order By: Relevance
“…76 Interestingly, in both studies, early (1 hour) conversion rates were significantly better with propafenone, suggesting a more delayed onset of action with amiodarone. Other small, randomized studies of acute AF conversion have found intravenous amiodarone to be similar to intravenous procainamide, 77 and in 1 trial, significantly less effective than magnesium sulfate. 78 Primary prevention of AF is a worthwhile goal that has been studied in 1 heart failure trial and extensively in patients recovering from open-heart surgery, in whom AF occurs in about 30% of patients.…”
Section: Amiodarone For Afmentioning
confidence: 88%
“…76 Interestingly, in both studies, early (1 hour) conversion rates were significantly better with propafenone, suggesting a more delayed onset of action with amiodarone. Other small, randomized studies of acute AF conversion have found intravenous amiodarone to be similar to intravenous procainamide, 77 and in 1 trial, significantly less effective than magnesium sulfate. 78 Primary prevention of AF is a worthwhile goal that has been studied in 1 heart failure trial and extensively in patients recovering from open-heart surgery, in whom AF occurs in about 30% of patients.…”
Section: Amiodarone For Afmentioning
confidence: 88%
“…Chapman et al 8 showed equal efficacy between amiodarone and procainamide in the management of atrial tachyarrhythmias among critically ill adults (71% effective for amiodarone compared with 70% for procainamide with no significant differences in time to conversion or AEs). The appropriateness of extrapolating this data to pediatric patients, who have both varied arrhythmic substrates and presumably different medication effects, is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In recurrent or refractory SVT, both intravenous amiodarone and procainamide have been administered, with variable success rates reported in the literature. [1][2][3][4][5][6][7][8] No studies to date, however, have compared these 2 medications in terms of efficacy and safety in the treatment of pediatric patients with SVT. The purpose of this study was to (1) compare the treatment efficacy of amiodarone versus procainamide in pediatric patients with recurrent SVT and (2) compare the adverse effects associated with the use of these 2 medications.…”
Section: Editorial See Page 115 Clinical Perspective On P 140mentioning
confidence: 99%
“…The drug was also found to be inferior to ibutilide in conversion of both atrial flutter (14% vs. 76%) and atrial fibrillation (21% vs. 51%) [17]. There was no difference in conversion efficacy of atrial tachycardia for procainamide vs. amiodarone in the critically ill (71% vs. 70%) [21].…”
Section: Class Ia Antiarrhythmic Medications Procainamidementioning
confidence: 99%